A Desain Aplikasi Penyewaan Tenda Berbasis Web Mobile Menggunakan Metode Customer Relationship Management (CRM) - Tri Hasanah Bimastari Aviani; Cindi Wulandari; Imam Agus Faisal (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The ACC Tent Lubuklinggau tent rental system currently still uses the manual method of providing information on tent units for rent as well as the traditional payment system which is considered inefficient because there are still many errors and even misunderstandings in providing information on available tent units. Customers must come directly to the website because there is no information system that makes it easy for customers to find information on properties for rent, such as:  Description of the tent unit, rental rates, available unit inventory based on rental days, and regular rental and payment systems. Of course this makes it difficult for customers, especially if the customer comes from outside, it is very detrimental for the customer when he spends a lot of energy and time to come, but the tent he rents is not available. CRM (Customer Relationship Management) is a strategy to learn more about the needs and characteristics of customers while building closer relationships with customers. Therefore, to overcome the above problems, we need a mobile web-based rental application that uses a customer relationship management (CRM) methodology to assist consumers in finding information regarding tent unit descriptions, rental rates, and available unit inventory. rental days and make it easy for customers to rent and pay rent online. The results of this study are in the form of a mobile web application that contains information about tents such as prices, inventory and rental systems, as well as online rentals. This system was created to assist customers in finding information before renting and can also rent online without having to come directly to ACC Tenda Lubuklinggau